2021
DOI: 10.1097/md.0000000000023804
|View full text |Cite
|
Sign up to set email alerts
|

The difference in heat transport characteristics of the heart and lung meridians

Abstract: Background: The vast majority of previous studies focused on the relationship between 1 meridian and 1 organ, and the comparison and specificity between 2 meridians is rarely explored. Thus, the aim of this study is to compare the heat transport characteristics between 2 different meridians and the specificity between them will also be investigated. Methods: The Lung and Heart meridians are chosen for comparison of 2 different meridians. We will enroll 120 subjects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Cited reference Author and publication year acupoint skin temperature between patients and the general population, the temperature difference between the unaffected and affected sides or the temperature difference in the patient's own treatment (Liu et al, 2020;Li et al, 2021;Reddy et al, 2023;Tu et al, 2023;Wang et al, 2023). An article published in 2012 shows asthma patients had significantly lower overall infrared radiation intensity at the left Taiyuan (LU 9) than that of healthy volunteers which suggested that IRT detection of acupoint temperature has a potential role in the diagnosis of diseases (Zhou et al, 2012).…”
Section: Rank Co-citation Countsmentioning
confidence: 99%
“…Cited reference Author and publication year acupoint skin temperature between patients and the general population, the temperature difference between the unaffected and affected sides or the temperature difference in the patient's own treatment (Liu et al, 2020;Li et al, 2021;Reddy et al, 2023;Tu et al, 2023;Wang et al, 2023). An article published in 2012 shows asthma patients had significantly lower overall infrared radiation intensity at the left Taiyuan (LU 9) than that of healthy volunteers which suggested that IRT detection of acupoint temperature has a potential role in the diagnosis of diseases (Zhou et al, 2012).…”
Section: Rank Co-citation Countsmentioning
confidence: 99%